The civil rights movement - Orr, Tamra (San Diego, Calif. : Blackbirch Press, 2004)
Profiles people who led the civil rights movement in the United States, including Rosa Parks, Asa Philip Randolph, Ida B. Wells-Barnett, and Booker T. Washington.
William Lloyd Garrison -- Frederick Douglass -- James Farmer -- Malcolm X.
Includes bibliographical references and index.
Keywords: African American civil rights workers -- Biography -- Juvenile literature; Civil rights workers -- United States -- Biography -- Juvenile literature; African Americans -- Civil rights -- History -- Juvenile literature; Civil right movements -- United States -- History -- Juvenile literature; Civil rights workers; Political activists; African Americans -- Civil rights -- History -- 20th century; Civil rights movements -- History -- 20th century; Race relations; African Americans -- Biography